Semiotics and iconology. New themes for an old confrontation - Lancioni, Tarcisio (E|C, 2020)
The essay proposes a reflection on the relationship between semiotics and iconology. A comparison in which semiotics has already dealt with but which today, with the diffusion of visual studies, takes on a different perspective that calls into question both semiotics and iconology, with regard to their respective abilities to deal with the “meaning of images”. In particular, we tried to understand which image of semiotics emerges from the point of view of iconology and visual studies.